Clinicopathological significance of platelet-derived growth factor B, platelet-derived growth factor recpertor-β, and E-cadherin expression in gastric carcinoma - Guo, Yi; Yin, Jiangyan; Zha, Lang; Wang, Ziwei (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : Platelet-derived growth factor B (PDGF-B), a vital growth factor which can induce angiogenesis and epithelial-mesenchymal transition (EMT), is important in the metastasis of many tumors. However, the roles of PDGF-B in gastric carcinoma are largely unknown. We investigated the correlation between PDGF-B, PDGFR-β and E-cadherin expression with the clinical features of gastric carcinoma patients to evaluate the relationship between PDGF-B signaling, E-cadherin and metastasis of gastric carcinoma, the correlation between PDGF-B and E-cadherin expression to assess the roles of PDGF-B signaling in metastasis of gastric carcinoma.. Material and methods: We detected expressions of PDGF-B, PDGFR-β and E-cadherin in gastric carcinoma tissues and normal gastric mucosa tissues of 64 patients with gastric carcinoma who had undergone surgical resection, and investigated their relationships with clinical features and the relationships between PDGF-B and E-cadherin expression in gastric carcinoma. Results: In surgical specimens, tumor cells expressed PDGF-B, and PDGFR-β was expressed by tumor stromal cells. E-cadherin was expressed by both tumor cells and normal gastric mucosa cells. Expressions of PDGF-B and PDGFR-β were increased in gastric carcinoma tissues (p < 0.05) and were positively correlated with the depth of cancer invasion, lymph node metastasis and TNM stage (p < 0.05). The expression of E-cadherin was reduced in gastric carcinoma tissues (p < 0.05) and was negatively correlated with the depth of cancer invasion, lymph node metastasis and TNM stage (p < 0.05). The correlation between PDGF-B and E-cadherin expression was negative (p < 0.05). Conclusion : Our data indicate that either the overexpression of PDGF-B and PDGFR-β or the underexpression of E-cadherin is correlated with cancer progression and lymphogenous metastasis of gastric carcinoma. The PDGF-B signal pathway might induce EMT by down-regulating expression of E-cadherin to promote metastasis of gastric carcinoma.